Dosage Form Of Classical Ayurvedic Formulations With Animal Origin Ingredients For Treatment Of Sexual Dysfunction , Vajikaran By Charak - Raza, Mazahir (International Research Journal of Ayurveda & Yoga, 2021)
The aim of this study was to draw the importance of ayurvedic aphrodisiac medicine based on animals . It is an overview of the use of animal ingredients in classical books of Ayurveda for treatment of Vajikarna , sexual dysfunction. For several hundred years these formulations are prescribed to energize, vitalize, and eventually to improve sexual functions. There are several formulations in which meat of different animals and birds is used as active ingredient. The dosage form of these formulations are pills, cake, soups, oil and boluses. The importance of ayurvedic aphrodisiac medicine based on animals cannot be denied but since these formulations not have been methodically tested by pharmaceutical companies, pharmaceutical scientists could undertake the research to validate the claims